Изменчивость размеров и формы женских шишек сосны пицундской (Pinus pityusa stev.) в насаждениях Крыма - Горлова, Е.М. (Промышленная ботаника, 2002)
Endogenic individual variability of morphometric peculiarities (e. i. strobile length and diameter) and a relative cone shape index (IFS) have been examined in the P. pityusa natural populations and an artificial stand of the Crimea. Values of variation coefficient (CV,%) and variation ranges of three parameters under study have been determined. Three classes of trees were distinguished within the given species using a IFS index: 1 – trees with the narrow-conic strobiles (IFS<0,56), 2 – with the ovate-conic strobiles (IFS=0,56 to 0,66), 3 – with the wide-conic strobiles (IFS>0,66).